2009
DOI: 10.1111/j.1530-0277.2009.00907.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol‐Induced Extracellular Signal Regulated Kinase: Role of Dopamine D1 Receptors

Abstract: The results of this study indicate that ethanol, similar to other addictive drugs, activates ERK in nucleus Acb and extended amygdala via a DA D(1) receptor-mediated mechanism. Overall, these results suggest that the D(1) receptors/ERK pathway may play a critical role in the motivational properties of ethanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
88
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 50 publications
(100 citation statements)
references
References 65 publications
9
88
1
Order By: Relevance
“…The same group then showed that injection of cocaine to mice induces the nuclear accumulation of active di-phospho ERK1/2 and that the activation of ERK is necessary for cocaine-induced IEG expression and CPP (Valjent et al 2000). Further work showed that phosphorylation of ERK1/2 in the ventral striatum is a common effect of all drugs of abuse including cocaine, amphetamine, morphine, nicotine, D9-tetrahydrocannabinol, methamphetamine, 3,4-methylenedioxy-methamphetamine (MDMA, also known as ecstasy), and ethanol (Valjent et al 2001;2004;Salzmann et al 2003;Ibba et al 2009). This activation appeared to be functionally important since pharmacological blockade of MEK, usually with SL327, an inhibitor of MEK that crosses the blood-brain barrier, prevented the long-term behavioral effects of these drugs.…”
Section: Extracellular Signal-regulated Kinase (Erk) Pathwaymentioning
confidence: 96%
“…The same group then showed that injection of cocaine to mice induces the nuclear accumulation of active di-phospho ERK1/2 and that the activation of ERK is necessary for cocaine-induced IEG expression and CPP (Valjent et al 2000). Further work showed that phosphorylation of ERK1/2 in the ventral striatum is a common effect of all drugs of abuse including cocaine, amphetamine, morphine, nicotine, D9-tetrahydrocannabinol, methamphetamine, 3,4-methylenedioxy-methamphetamine (MDMA, also known as ecstasy), and ethanol (Valjent et al 2001;2004;Salzmann et al 2003;Ibba et al 2009). This activation appeared to be functionally important since pharmacological blockade of MEK, usually with SL327, an inhibitor of MEK that crosses the blood-brain barrier, prevented the long-term behavioral effects of these drugs.…”
Section: Extracellular Signal-regulated Kinase (Erk) Pathwaymentioning
confidence: 96%
“…Acute alcohol and other drugs of abuse are known to independently produce increases in active ERK (pERK), involved in the transduction of dopamine signaling, in the nucleus accumbens and other brain regions (Ibba et al, 2009). Indeed, the acute upregulation of pERK seen after alcohol administration appears to be mediated, at least in part, through dopamine D1 receptors as D1 inhibition prevents dose-dependent increases in ERK phosphorylation induced by alcohol (Ibba et al, 2009).…”
Section: Neurotransmitter Systemsmentioning
confidence: 99%
“…Thirdly, activation of ERK is critical for long-term potentiation, a phenomenon of long-lasting synaptic plasticity that allows the characterization of the role of transduction molecules in the processes of learning and formation of long-term memories (Giovannini 2006;Sweatt 2004;Vara et al 2009). Fourthly, in mature neurons, the activation of ERK is involved in the mechanism of action of addictive drugs (Acquas et al 2007;Ibba et al 2009;Lu et al 2006;Valjent et al 2004) and in their positive motivational properties as determined by CPP Girault et al 2007;Lu et al 2006).…”
Section: Introductionmentioning
confidence: 99%